2017
DOI: 10.4103/ijccm.ijccm_240_16
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care nurses\' attitude on palliative and end of life care

Abstract: Background:Intensive Care Unit (ICU) nurses have a vital role in the implementation of end of life (EOL) care. There is limited data on the attitude of ICU nurses toward EOL and palliation.Aim:This study aimed to investigate knowledge, attitude, and beliefs of intensive care nurses in eastern India toward EOL.Materials and Methods:A self-administered questionnaire was distributed to delegates in two regional critical care nurses' training programs.Results:Of 178 questionnaires distributed, 138 completed, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…15 An Indian study conducted in 2017 to assess the attitudes, beliefs, and knowledge of nurses working in critical care setup observed that knowledge and attitude toward EOLC was influenced by the religious inclination and the work experience of the nurses. 14 Improvement in knowledge of doctors with experience was also found in our study. Subsequent study can be planned to evaluate the effect of religious inclinations of the doctors on their attitude toward EOLC.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…15 An Indian study conducted in 2017 to assess the attitudes, beliefs, and knowledge of nurses working in critical care setup observed that knowledge and attitude toward EOLC was influenced by the religious inclination and the work experience of the nurses. 14 Improvement in knowledge of doctors with experience was also found in our study. Subsequent study can be planned to evaluate the effect of religious inclinations of the doctors on their attitude toward EOLC.…”
Section: Discussionsupporting
confidence: 83%
“…This need for further education and training for doctors as well as nurses was consistent with the findings of other studies. 10,[12][13][14][15][16] Vejlgaard et al studied the attitudes of Danish doctors and nurses to palliative and terminal care and found that nurses were more likely than doctors to perceive palliative/terminal care as rewarding. 15 Similar to the findings in our study, they also reported that there was a lack of education regarding palliative care among healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Religiousness was associated strongly with a greater desire to initiate EOL discussions when indicated. 26 The right to die with dignity including, deciding where to die , who is present and treatment options is still not recognized in Jordanian society because of religious values. Recognizing and addressing cultural and religious/spiritual values is a critical aspect of providing goal-concordant care for patients facing a serious illness, especially at the end of life.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, the results of a study [ 39 ] demonstrated that it was more acceptable for the emergency team to start treatment and then leave it if the expected benefit was not obtained than “doing absolutely nothing” (p. 41). Death can be seen as a failure in the care provided and many professionals do not notice the value of choices and end-of-life desires, such as dying at home and in the presence of relatives [ 40 ].…”
Section: Discussionmentioning
confidence: 99%